Rancang Bangun Sistem Informasi Helpdesk Berbasis Web Menggunakan Metode Agile (Studi Kasus : PT Geotech Efathama) - Gilang Pratama, Ardhiat; Setiawan Cahyadi, Dwiky; Iskandar, Harry; Djutalov, Roeslan (CV. Shofanah Media Berkah, 2024)
A web-based helpdesk information system plays a crucial role in enhancing the efficiency and quality of services in companies. This research aims to design and develop a web-based helpdesk information system using the Agile method, with a case study at PT Geotech Efathama. The Agile method was chosen for its flexibility and adaptability to dynamic user needs. The designed system includes features for issue reporting, task scheduling, and ticket resolution tracking, streamlining the management of technical issues. The research results indicate that the Agile method improves user satisfaction and accelerates problem-solving processes..